2022
DOI: 10.3390/ijerph19052893
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling between Economic Development and Carbon Emissions and Its Driving Factors: Evidence from China

Abstract: Analyzing the relationship between economic development and carbon emissions is conducive to better energy saving and emission reduction. This study is based on the panel data of China’s carbon emissions, from 2009 to 2019, and quantitative analysis of the relationship between carbon emissions and economic development through the Tapio decoupling model and the Logarithmic Mean Divisia Index (LMDI) decomposition model. The results show that: First, carbon emission and economic development are increasing year by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 46 publications
4
37
0
Order By: Relevance
“…The main reason can be considered as a well-functioning financial sector may provide more financing at a lower cost, thus more and more capital flows into environmental protection and energy conservation projects and enterprises, promoting the rapid development of the environmental protection industry and driving the green transformation and upgrading of traditional industries as well [ 10 ]. Besides, the development of finance prompts listed companies to adopt energy-saving technologies and finally achieve the goal of reducing environmental pollution [ 12 , 13 ]. Likewise, Shahbaz et al [ 14 ] showed that inefficient use of energy has a significant and negative influence on environmental quality, while the adoption of high-efficiency technologies at the production and consumption levels can build a cleaner environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main reason can be considered as a well-functioning financial sector may provide more financing at a lower cost, thus more and more capital flows into environmental protection and energy conservation projects and enterprises, promoting the rapid development of the environmental protection industry and driving the green transformation and upgrading of traditional industries as well [ 10 ]. Besides, the development of finance prompts listed companies to adopt energy-saving technologies and finally achieve the goal of reducing environmental pollution [ 12 , 13 ]. Likewise, Shahbaz et al [ 14 ] showed that inefficient use of energy has a significant and negative influence on environmental quality, while the adoption of high-efficiency technologies at the production and consumption levels can build a cleaner environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All the studies by (Wu et al, 2019;Mo and Wang., 2021;Tian and Lin., 2021) have concluded that the relationship between the two gradually tends toward low-carbon economic development, providing a scientific theoretical basis for adopting emission reduction measures to reach the peak in each region. In another study, Zhao et al (2022) argued that carbon emissions and economic growth are closely related and generally do not cross over in the long run; this view was also supported by (Myszczyszyn and Suproń, 2021) study of carbon emissions and economic growth in V4 countries (namely Czech Republic, Hungary, Poland, and Slovakia). However, there is still a degree of dependence of economic growth on carbon emissions.…”
Section: The Relationship Between Carbon Emissions and Economic Growthmentioning
confidence: 81%
“…First, some researchers believe that the carbon emissions generated in the process of using cultivated land resources only include the direct or indirect greenhouse gas carbon emission caused by human production and operation activities [ 32 , 33 ]. Second, others believe that the carbon emissions generated in the process of utilizing cultivated land resources should also include the carbon sink effect of cultivated land resources and outputs [ 34 , 35 ]. Based on the published research results, more researchers focus on the first cognition [ 28 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%